The Impact Of Finansial and Non-Finansial Incentives On Employee Performance : Case Study Of Perbankan Company - Andyni Dewi Lestari; Budi Permana Yusuf (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aims to find out whether there is an influence between providing incentives and employee performance of PT Bank Panin Indonesia Tbk KCU Menara Imperium. This study uses data collection methods by distributing questionnaires. The sample population used in this study were employees at Pt Bank Panin Indonesia, with as many as 66 respondents. Hypothesis testing in this study uses validity test, reliability test, classical assumption test with simple linear regression model, t test and coefficient of determination (R2). The results of this study indicate that the incentive t- test partially has a positive and significant effect on employee performance. With t value of 5.477. Through testing, the coefficient of determination (R square) is 0.319 or 31.9%, which indicates that the ability of the incentive variable to explain the employee performance variable is 31.9%, and the remaining 68.10% is influenced by other factors not used in this study.